Diagnosis of the relationship between soil and plant degradation in a Eucalyptus urophylla cultivation area with the presence of termites and ants (Research, Society and Development, 2021)
Termites and ants are biotic agents with a high level of diversification, indicating soil degradation and nutritional deficiency. With the damage caused by them, in the soil and in eucalyptus plants, it is necessary to control these pests, so that, for the success of the application of integrated pest management, the population assessment of these individuals is essential, and it is essential to know how they are distributed in the field. Thus, the objective was to investigate the dynamics of spatial distribution of ant and termite nests in an area of ​​eucalyptus planted forest, as well as to study the impact caused by these pests on the soil and on the plant. In the evaluation of the attributes in the planting of Eucalyptus urophylla, there were five: (1) the number of dead trees, (2) the number of anthill and (3) the number of termite nests, (4) the area of ​​the anthills and (5) the area of ​​the termite nests. For the ant nest and termite attributes, 3 to 5 samples from the areas were collected, then averaged in order to correspond to each georeferenced point. There was an irregular distribution of ant and termite nests throughout the study area, attenuating the invasion of grass, mainly in places with a greater number of ant nests, recommending the maintenance of this population due to these biotic agents in the area.